The National Planning Policy Framework and Archaeology: A Response by RESCUE - The British Archaeological Trust - RESCUE (The British Archaeological Trust) (Papers from the Institute of Archaeology, 2013)
The National Planning Policy Framework (NPPF) delivers a concise set of policies which the development industry can view (with some satisfaction given its brevity) as being the basic standard principles by which their work must be conducted. The core of sensible planning is here – care for the economy, consideration of the environment, quality of design and, crucially for our profession, conservation and enhancement of the Historic Environment. The authors (Joe Flatman and Dominic Perring) correctly highlight the very inclusion of heritage as a welcome advancement on previous regimes.
Keywords: National Planning Policy Framework; planning; development